Effect of Auditory Constraints on Motor Performance Depends on Stage of Recovery Post-Stroke - Aluru, Viswanath; Lu, Ying; Leung, Alan; Verghese, Joe; Raghavan, Preeti (Frontiers in Neurology, 2014)
In order to develop evidence-based rehabilitation protocols post stroke, one must first reconcile the vast heterogeneity in the post-stroke population and develop protocols to facilitate motor learning in the various subgroups. The main purpose of this study is to show that auditory constraints interact with the stage of recovery post stroke to influence motor learning. We characterized the stages of upper limb recovery using task-based kinematic measures in twenty subjects with chronic hemiparesis, and used a bimanual wrist extension task using a custom-made wrist trainer to facilitate learning of wrist extension in the paretic hand under four auditory conditions: 1) without auditory cueing; 2) to non-musical happy sounds; 3) to self-selected music; and 4) to a metronome beat set at a comfortable tempo. Two bimanual trials (15 s each) were followed by one unimanual trial with the paretic hand over six cycles under each condition. Clinical metrics, wrist and arm kinematics and electromyographic activity were recorded. Hierarchical cluster analysis with the Mahalanobis metric based on baseline speed and extent of wrist movement stratified subjects into three distinct groups which reflected their stage of recovery: spastic paresis, spastic co-contraction, and minimal paresis. In spastic paresis, the metronome beat increased wrist extension, but also increased muscle co-activation across the wrist. In contrast, in spastic co-contraction, no auditory stimulation increased wrist extension and reduced co-activation. In minimal paresis, wrist extension did not improve under any condition. The results suggest that auditory task constraints interact with stage of recovery during motor learning after stroke, perhaps due to recruitment of distinct neural substrates over the course of recovery. The findings advance our understanding of the mechanisms of progression of motor recovery and lay the foundation for personalized treatment algorithms post stroke.